Penyuluhan tentang Imunisasi Dasar, Vitamin A dan Tumbuh Kembang pada Bayi dan Balita di Wilayah Puskesmas Jenggot Kota Pekalongan - Putri Andanawarih; Miftachul Jannah (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Supporting and maintaining surveillance of immunization programs and provision of Vitamin A in Indonesia is one of the efforts in reducing MMR and IMR. Immunization is one of the most effective public health interventions in preventing morbidity and mortality. Vitamin A is one of the important nutrients that is fat soluble and stored in the liver, cannot be produced by the body, so it must be fulfilled from the outside (essential), functioning to vision, growth and increase the body's resistance to disease. Vitamin A is useful for reducing mortality and morbidity, because of that vitamin A can increase the body's resistance to infectious diseases such as measles, diarrhea, and Acute Respiration Infection (ISPA). Other consequences that have a very serious impact from Vitamin A Deficiency (KVA) are night blindness and other manifestations of xeropthalmia including corneal damage and blindness. The team conducted community service under the title